[Household Arts, Weeks Administration Building, Dormitory] - Frank Aston::::::photographer:::
Front elevations of Household Arts, Weeks Administration Building, Dormitory; Probably later date than Aston Photo no. 203 -- note growth of plantings in front of buildings